2022
DOI: 10.1002/solr.202200221
|View full text |Cite
|
Sign up to set email alerts
|

Furfurylammonium as a Spacer for Efficient 2D Ruddlesden–Popper Perovskite Solar Cells

Abstract: 2D perovskites have recently emerged as promising materials for solar cells due to their appealing ambient stability and structural diversity. The organic spacer cation plays an important role in the stability and properties of the 2D perovskites. Herein, a new organic ammonium cation, 2‐furfurylammonium (FuMA+), is developed as the spacer cation for 2D Ruddlesden–Popper perovskites. Thin films of (FuMA)2(MA)4Pb5I16 with increased crystal size and enhanced vertical orientation are obtained via an additive‐assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Planar PSCs with a structure of ITO/PEDOT:PSS/perovskite/PCBM/BCP/Ag were fabricated to study the photovoltaic performance of 2D perovskite films. Note that, when we prepared the manuscript, Zheng et al reported FuMAI for a 2D RP perovskite with the formula (FuMA) 2 (MA) 4 Pb 5 I 16 and achieved a PCE of 15.66% for n–i–p structured devices using an additive-assisted film-forming technique . As shown in Figure a, the THFMA-Pb device shows a PCE of 13.79%, with a current density ( J SC ) of 18.73 mA cm –2 , an open-circuit voltage ( V OC ) of 1.018 V, and a fill factor (FF) of 70.30%.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Planar PSCs with a structure of ITO/PEDOT:PSS/perovskite/PCBM/BCP/Ag were fabricated to study the photovoltaic performance of 2D perovskite films. Note that, when we prepared the manuscript, Zheng et al reported FuMAI for a 2D RP perovskite with the formula (FuMA) 2 (MA) 4 Pb 5 I 16 and achieved a PCE of 15.66% for n–i–p structured devices using an additive-assisted film-forming technique . As shown in Figure a, the THFMA-Pb device shows a PCE of 13.79%, with a current density ( J SC ) of 18.73 mA cm –2 , an open-circuit voltage ( V OC ) of 1.018 V, and a fill factor (FF) of 70.30%.…”
mentioning
confidence: 96%
“…Note that, when we prepared the manuscript, Zheng et al reported FuMAI for a 2D RP perovskite with the formula (FuMA) 2 (MA) 4 Pb 5 I 16 and achieved a PCE of 15.66% for n−i−p structured devices using an additive-assisted film-forming technique. 40 As shown in Figure 3a, the THFMA-Pb device shows a PCE of 13.79%, with a current density (J SC ) of 18.73 mA cm −2 , an open-circuit voltage (V OC ) of 1.018 V, and a fill factor (FF) of 70.30%. The optimized FuMA-Pb devices show a significantly enhanced J SC of 20.84 mA cm −2 , an improved V OC of 1.054 V, and a very notable FF of 81.95%, yielding an excellent PCE of 18.00% with negligible J−V hysteresis.…”
mentioning
confidence: 98%
“…These results indicate that the grain size can be tailored by changing the molecular weight of the PEG additive, which is attributable to the impact of the PEG additive on the crystallization kinetics of the perovskite film . PEG is often considered a Lewis base due to the ether group C–O–C with lone-pair electrons and which allows the formation of Lewis acid–base interactions with the positively charged defects such as undercoordinated Pb 2+ in the CsPbI 2 Br perovskite, while Pb 2+ is regarded as a Lewis acid since Pb­(II) halides prefer to accept iodide anions to form iodo-plumbate anions such as [Pb 3 I 10 ] 4– and [Pb 5 I 16 ] 6– . The formed Lewis acid–base interaction between PEG and Pb 2+ allows us to tune the crystallization of the CsPbI 2 Br perovskites and further impacts the morphology and optoelectronic properties in perovskite films by changing the PEG molecular weight in the following aspects . First of all, the increase in the PEG molecular weight from 6k to 10k results in an increase in the nucleation energy barrier to reduce the quantity of the perovskite crystal nucleus .…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al observed that replacing either MAI with MACl or PEAI with PEACl in precursor solutions of PEA ⟨ n ⟩ ≥ 6 RP halide perovskite significantly improved crystallinity, reduced defect density, and enhanced device stability in inert atmosphere . Other reports have also shown MACl to improve crystallinity and grain orientation. , …”
Section: Stability Of 3d and 2d Halide Perovskitesmentioning
confidence: 97%
“…524 Other reports have also shown MACl to improve crystallinity and grain orientation. 90,525 The A′-site itself can be engineered to improve film quality. Cheng et al incorporated amylammonium (AA + ) into PEA ⟨n⟩ ≥ 5 halide perovskites to relax residual strain in the lattice.…”
Section: Strengthen Interlayer Interactionsmentioning
confidence: 99%